Interaction of surface waves with an actuated submerged flexible plate: Optimization for wave energy extraction. (August 2018) - Desmars, N.; Tchoufag, J.; Younesian, D.; Alam, M.-R.
Abstract: We investigate the interaction of linear surface waves with a submerged wave energy converter which consists of a submerged flexible plate actuated by one (or more) units of power take off (PTO), each modeled as a combination of a linear spring and a linear damper. We develop a wave-flexible structure interaction model through modal decomposition of the structure deformations, and use Boundary Element Method to find hydrodynamic coefficients of each deformation mode of the structure. We validate our methodology with existing analytical results of hydro-elasticity. We then perform a case study and obtain the maximum efficiency (or Capture Width Ratio (CWR)) of our wave energy converter when excited by monochromatic waves through a comprehensive parametric study of the device parameters (e.g. rigidity of the plate, and location and characteristics of the PTO units). In the absence of viscous effects, the device can reach an efficiency as high as 80%. We find that the efficiency is more sensitive to the location of the PTOs than to their damping coefficients. For a range of plate length to wavelength ratios (close to unity) and with a single PTO unit, the optimal PTO location is past the middle of the plate (along the incident wave direction). This location is nearly independent of the rigidity of the plate although the resulting CWR depends on the rigidity. When two PTO units are used the optimal configuration of PTOs depends on the plate's aspect ratio and its placement with respect to the incident wave: the two PTOs may need to be at the same location, lined up along the direction of wave propagation, or placed side-by-side perpendicular to the direction of the wave propagation.